Synthesis and characterization of cyclohexene oxide functional polystyrene macromonomers by ATRP and their use in photoinitiated cationic polymerization - Degirmenci, Mustafa; Izgin, Oner; Acikses, Aslisah; Genli, Nasrettin (Elsevier, 2010)
In this study, a novel well-defined macromonomer of epoxy end-functionalized polystyrene was synthesized by atom transfer radical polymerization (ATRP). The compound 3-cyclohexenylmethyl-2-bromopropanoate was synthesized by the condensation of 3-cyclohexene-1-methanol with 2-bromopropanoyl bromide. Subsequently, the epoxidation of the obtained 3-cyclohexenylmethyl-2-bromopropanoate using 3-chloroperoxybenzoic acid results in a new epoxy functional ATRP initiator. The ATRP of styrene (St) in bulk at 110 degrees C, by means of this initiator in conjunction with the cuprous complex Cu(I)Br/bipyridine, yields a well-defined macromonomer of polystyrene with an epoxy end group. GPC, IR, and H-1 NMR analyses revealed that a low-polydispersity polystyrene with the desired functionality at the end of the chain was obtained. The photoinduced cationic polymerization of this macromonomer yielded graft and block copolymers. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Atom transfer radical polymerization (ATRP); Functional polymer; Macromonomer; Free radical promoted cationic polymerization; Copolymerization